Penerapan Program "Sehat Kerja" Berbasis Edukasi Dan Skrining Tekanan Darah Pekerja Proyek Pembangunan Gedung - Dealita Khairani Daulay; Murni Noviani Nasution; Balqis Nurmauli Damanik; Asnita Yani; Annisa FebrianaSiregar; Selamat Tuahta Sipayung; Solihin Solihin; Yoseph Steven Tambunan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
Hypertension remains a leading noncommunicable disease and a major contributor to cardiovascular morbidity among the working-age population. Construction workers face compounded risk from physical workload, heat exposure, and long working hours, yet structured on-site cardiovascular screening is rarely provided. This community service program aimed to improve construction workers' knowledge of hypertension, conduct blood pressure screening, and strengthen occupational health and safety (K3) culture on a building construction project. The program used a One Group Pretest-Posttest Design involving 21 male construction workers selected through total sampling at Universitas Bunda Thamrin building project, Medan. Activities included preparatory coordination, health education using leaflet, slide presentation and a 5-minute video, interactive discussion, blood pressure screening with a calibrated digital sphygmomanometer, individual counseling for workers with elevated readings, and post-test evaluation. Knowledge scores were analyzed using paired t-test, n-gain, and Cohen's d. Mean knowledge scores increased significantly from 61.5 (SD = 8.4) to 88.2 (SD = 6.1), with a mean difference of 26.7 points (p < 0.001; n-gain = 0.69, medium-high category; Cohen's d = 3.63, very large effect). Blood pressure screening identified 10 workers (47.6%) with normal readings, 5 (23.8%) with prehypertension, 4 (19.1%) with grade I hypertension, and 2 (9.5%) with grade II hypertension. The "Sehat Kerja" program was effective in improving workers' knowledge and identifying at-risk individuals early. Integration of this program with the enterprise Occupational Safety and Health Committee (P2K3) is recommended.